A Quest for Longevity? A New Approach to the Earliest Testimonies of Medieval Alchemy - Heiduk, Matthias (Micrologus, 2018)
Medieval Europe learned about alchemy through the translation of Arabic treatises into Latin. What sparked the curiosity regarding this new knowledge? Was it perhaps the promise of the life-extending effect of the elixir that inspired its initial reception? Historical research has been unable to answer this obvious question so far. This paper merely takes a few cautious steps on the road towards filling the gaps about early alchemy in the Medieval West. It focuses on the problems of the earliest textual witnesses in Latin from the XIIth century (Liber Morieni, Septem tractatus Hermetis, Tabula smaragdina) and adopts a systematic approach by undertaking a stringent comparison of these early alchemica with a large amount of Latin translations from Arabic of this time facilitated by the "Arabic-Latin-Corpus" of digitally-converted texts. This approach disproves two assumptions regularly featured in the research literature. On the one hand, the Liber dabessi - a combination of the Tabula smaragdina and an alchemical compilation - is not a translation by Plato of Tivoli and probably not a XIIth century translation at all. On the other hand, the Septem tractatus Hermetis are not a translation by Robert of Chester, but they show some remarkable accordance with specific words and phrases used in the Turba philosophorum as well as by John of Seville. The analysis of the Liber Morieni gains less clear results. They neither fully approve nor exclude the commonly attested attribution to Robert of Chester. The second part of the paper collects the statements in these early translations on the possibility of prolonging life. The third part focuses on the question of whether anything can be derived from the historical context of these translations regarding the motivation of the translators in turning towards alchemy. The concluding resume points to possible further research avenues built on the basis of this paper.
CRIS-Team WoS Importer:2019-08-13

A Quest for Longevity? A New Approach to the Earliest Testimonies of Medieval Alchemy - Heiduk, Matthias (Longevity and Immortality: Europe - Islam - Asia, 2018)

Beyond Astrology - Mantic Practices as Decision Support at Medieval Western Courts - Heiduk, Matthias (Unterstützung bei herrscherlichem Entscheiden: Experten und ihr Wissen in transkultureller und komparativer Perspektive, 2021)

Games and Prognostication: The Examples of Libro de los Juegos and De vetula - Heiduk, Matthias (Prognostication in the Medieval World: A Handbook: In Collaboration with Avriel Bar-Levav, Charles Burnett, Michael Grünbart and Petra G. Schmidl, 2021)

Orakeln mit Losbüchern | Oracle with Lot Books - Heiduk, Matthias (Zeichen der Zukunft: Wahrsagen in Ostasien und Europa | Signs of the Future: Divination in East Asia and Europe | Ci ming dang he: Ou Ya de bu shu, shu shu yu shen shu 此命當何: 歐亞的卜術，數術與神術, 2021)

Prognostication in Medieval Learned Magic of the Western Christian World - Heiduk, Matthias; Otto, Bernd-Christian (Prognostication in the Medieval World: A Handbook: In Collaboration with Avriel Bar-Levav, Charles Burnett, Michael Grünbart and Petra G. Schmidl, 2021)

Prognostication in the Medieval Western Christian World - Heiduk, Matthias (Prognostication in the Medieval World: A Handbook: In Collaboration with Avriel Bar-Levav, Charles Burnett, Michael Grünbart and Petra G. Schmidl, 2021)

Prognostication in the Medieval World: A Handbook: In Collaboration with Avriel Bar-Levav, Charles Burnett, Michael Grünbart and Petra G. Schmidl - Heiduk, Matthias; Herbers, Klaus; Lehner, Hans Christian (Walter de Gruyter, 2021)